(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article deals in detail with the linguocultural image of traditional songs, which are the pearl of the spiritual culture of the Kazakh people. The contents of the texts of traditional songs of Kazakh people reflect the peculiarities of mentality, ethnic, linguocultural perception of music and folded history of the Great Steppe, the variety of everyday life, social consciousness and world picture. Traditional Kazakh folk songs are grouped according to the content-structural system as songs born in connection with ancient beliefs, songs born in connection with economy and occupation, household and ritual songs. Traditional Kazakh songs have a linguistic examination of the lyrics reflecting the brevity of the song. The lexico-semantic specificity in the linguocultural aspect of the texts of traditional songs of the Kazakh people is the richest in philosophical deep meaning and didactic content, various expressions and emotions, parables-sentences and aphorisms, phrases and syntactic parallelisms. In the traditional song texts of the Kazakh people on the basis of specific examples the emotive lexicon and linguocultures, connotations carrying semantic and stylistic meaning are differentiated. The functional activity of such pictorial means as rhythm, noise, rhyme, timbre, intonation, metaphor generating the figurative artistic image, comparison, epithet, parallelism, symbolism, personification that make up the harmony of melody and words in a song text is analyzed.